Quality of life in a randomized trial of early closure of temporary ileostomy after rectal resection for cancer (EASY trial). Issue 3 (23rd November 2017) - Park, J.; Danielsen, A. K.; Angenete, E.; Bock, D.; Marinez, A. C.; Haglind, E.; Jansen, J. E.; Skullman, S.; Wedin, A.; Rosenberg, J.
Abstract : Background: A temporary ileostomy may reduce symptoms from anastomotic leakage after rectal cancer resection. Earlier results of the EASY trial showed that early closure of the temporary ileostomy was associated with significantly fewer postoperative complications. The aim of the present study was to compare health‐related quality of life (HRQOL) following early versus late closure of a temporary ileostomy. Methods: Early closure of a temporary ileostomy (at 8–13 days) was compared with late closure (at more than 12 weeks) in a multicentre RCT (EASY) that included patients who underwent rectal resection for cancer. Inclusion of participants was made after index surgery. Exclusion criteria were signs of anastomotic leakage, diabetes mellitus, steroid treatment, and signs of postoperative complications at clinical evaluation 1–4 days after rectal resection. HRQOL was evaluated at 3, 6 and 12 months after resection using the European Organisation for Research and Treatment of Cancer (EORTC) questionnaires QLQ‐C30 and QLQ‐CR29 and Short Form 36 (SF‐36®). Results: There were 112 patients available for analysis. Response rates of the questionnaires were 82–95 per cent, except for EORTC QLQ‐C30 at 12 months, to which only 54–55 per cent of the patients responded owing to an error in questionnaire distribution. There were no clinically significant differences in any questionnaire scores between the groups at 3, 6 or 12 months. Conclusion: Although the randomized study found that early closure of the temporary ileostomy was associated with significantly fewer complications, this clinical advantage had no effect on the patients' HRQOL. Registration number: NCT01287637 (https://www.clinicaltrials.gov ). Abstract : No different after early ileostomy closure